Carbide-free one-zone sulfurization method grows thin MoS2 layers on polycrystalline CVD diamond - Sojková, Michaela; Siffalovic, Peter; Babchenko, Oleg; Vanko, Gabriel; Dobročka, Edmund; Hagara, Jakub; Mrkyvkova, Nada; Majková, Eva; Ižák, Tibor; Kromka, Alexander; Hulman, Martin (Scientific reports, 2019)
The last few decades faced on the fabrication of advanced engineering materials involving also different composites. Here, we report on the fabrication of few-layer molybdenum disulfide on top of thin polycrystalline diamond substrates with a high specific surface area. In the method, pre-deposited molybdenum coatings were sulfurized in a one-zone furnace at ambient pressure. As-prepared MoS2 layers were characterized by several techniques including grazing-incidence wide-angle X-ray scattering, atomic force microscopy, scanning electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy. We found out that the initial thickness of Mo films determined the final c-axis crystallographic orientation of MoS2 layer as previously observed on other substrates. Even though it is well-known that Mo diffuses into diamond at elevated temperatures, the competing sulfurization applied effectively suppressed the diffusion and a chemical reaction between molybdenum and diamond. In particular, a Mo2C layer does not form at the interface between the Mo film and diamond substrate. The combination of diamond high specific surface area along with a controllable layer orientation might be attractive for applications, such as water splitting or water disinfection.